ANALISIS PENDAPATAN PETERNAKAN SAPI POTONG MELALUI PENGOLAHAN PUPUK ORGANIK (Studi Kasus Pada P4S Ramah Lingkungan Desa Galung Kecamatan Barru Kabupaten Barru Provinsi Sulawesi Selatan) - Nurjannah Bando (JURNAL LENTERA BISNIS, 2023)
This study aims to analyze the income of beef cattle farming through organic fertilizer processing in P4S Ramah Lingkungan, Galung Village, Barru District, Barru Regency, South Sulawesi Province. The research method used purposive sampling with the data of organic fertilizer income in 2018, 2019, and 2020. The results of the study show that the income of beef cattle farming through organic fertilizer processing in P4S Ramah Lingkungan, Barru Regency, South Sulawesi Province has increased from period to period. In 2018, the income was Rp. 24,038,547,-, in 2019 it was Rp. 25,928,667,-, and in 2020 it was Rp. 31,825,827,-. The R/C ratio analysis indicates that organic fertilizer processing business has a viable profit potential.Key words: Farm Income, Beef Cattle, Organic Fertilizer Processing.